A Critical Discourse Analysis of Sexual Harassment Against Women in Online Mass Media - Praminatih, Gusti Ayu; Nafiah, Homsatun (Humanis; Vol 26 No 2 (2022), 2022)
This study used Fairclough's critical discourse analysis theory to analyse the news articles published in Magdalene ??and Femina magazines in 2020. The authors particularly emphasised finding one of three aspects of Fairclough's socio-cultural practice: power. From this point, the authors attempted to find out the depiction of women and the stance of the contributors in the news articles about sexual harassment. This study found that the aspect of power constructed by contributors from news articles and magazines depicted women and men as vulnerable groups to sexual harassment. However, the harassment is described as still predominantly experienced by women. The findings also suggested that the contributors attempted to oppose male domination and power relations in the scope of work, especially in cyber sexual harassment.